2005
DOI: 10.1038/sj.gt.3302471
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation of immature and mature dendritic cells: implications for dendritic cell-based vaccines

Abstract: Until now, studies utilizing mRNA electroporation as a tool for the delivery of tumor antigens to human monocyte-derived dendritic cells (DC) have focused on DC electroporated in an immature state. Immature DC are considered to be specialized in antigen capture and processing, whereas mature DC present antigen and have an increased T-cell stimulatory capacity. Therefore, the consensus has been to electroporate DC before maturation. We show that the transfection efficiency of DC electroporated either before or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 52 publications
(63 reference statements)
5
64
1
Order By: Relevance
“…Recently, we have reported the novel vaccine delivery system, R8-Lip, which can for CTL induction [24,26]. In the present study, we also found that transduction of mDCs with R8-Lip was preferrential over transduction of iDCs.…”
Section: Discussionsupporting
confidence: 70%
“…Recently, we have reported the novel vaccine delivery system, R8-Lip, which can for CTL induction [24,26]. In the present study, we also found that transduction of mDCs with R8-Lip was preferrential over transduction of iDCs.…”
Section: Discussionsupporting
confidence: 70%
“…20 Electroporation of mRNA is a commonly used method to load dendritic cells with tumor-associated antigens, so they can be used as tumor vaccines. This technique yields high numbers of viable, transgene expressing dendritic cells, [21][22][23][24] adult stem cells, mesenchymal cells, phytohemagglutinin-stimulated T-cells 25 and CD40-activated normal B-cells, 26,27 but, to our knowledge, has not been used for CLL cells.…”
Section: Introductionmentioning
confidence: 99%
“…It would be the possible reason that immature DCs and conventional cultivated mature DC vaccines was not satisfactory in clinical use. Therefore, further study of the DC migration ability under different maturation stimulating conditions should be important for the design of effective tumor immunotherapy (36,37).…”
Section: Discussionmentioning
confidence: 99%